Les Canadiens français, l'histoire et la démocratie: l'interprétation de Pierre Elliott Trudeau - Ouellette, Mélanie (Mens, 2000)
Keywords: Trudeau, Pierre Elliott

Les signatures amérindiennes: essai d’interprétation des traités de paix de Montréal de 1700 et de 1701 - Guillaud, Yann; Delâge, Denis; D'avignon, Mathieu (Recherches amérindiennes au Québec, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal

Analyse et interprétations du génocide rwandais: nouveau fondement identitaire pour des rescapés du génocide dans la diaspora rwandaise de Montréal - Payette, Dominique (Université du Québec à Montréal, 2003)
Keywords: Rwandais

Le ciné-club étudiant au Québec, un véhicule d'ouverture à la modernité culturelle, 1949-1970 - Ménard, Olivier (Université de Sherbrooke, 2006)
Keywords: Cinéma; Jeunesse étudiante catholique; Office national du film; Étudiants

Le théâtre d'intervention et les jeunes de la rue - Dagenais, Bernard (Université du Québec à Montréal, 2001)
Keywords: Itinérance; Théâtre

Vers le bien et le beau: histoire de l'École de musique Vincent d'Indy: 1932-2007 - Laperle, Dominique (GID, 2007)
Keywords: Communautés religieuses; Musique; Soeurs des Saints Noms de Jésus et de Marie; École Vincent-D'Indy

C'était du spectacle!: l'histoire des artistes transsexuelles à Montréal, 1955-1985 - Namaste, Viviane (McGill-Queen's University Press, 2005)
Keywords: Cabarets

Création d'un numéro de variétés suivie d'une réflexion sur l'évolution du travestisme à Montréal, de 1969 à 2000 - Gauthier, Ives (Université du Québec à Montréal, 2003)
Keywords: Théâtre

Les représentations de la féminité et de la masculinité à travers le thème des rapports amoureux dans la chanson populaire francophone consommée au Québec, 1960-1990 - Ouellette, Myrthô (Université de Sherbrooke, 2006)
Keywords: Chanson; Musique

Les "musiques émergentes" à Montréal: devenir-ensemble et singularité - Lussier, Martin (Université de Montréal, 2008)
Keywords: Musicien; Musique

LA PALME, BÉATRICE (Issaurel) - Lefebvre, Marie-Thérèse (Dictionnaire biographique du Canada, 2005)

Albert Tessier et l'essor du cinéma clérical - Lacasse, Germain (1937: un tournant culturel, 2009)
Keywords: Cinéma

Les représentations de la femme dans l’œuvre scénique de Diane Dufresne, 1975-1984 - Lafrenière, Marilyne (Université du Québec à Trois-Rivières, 2008)
Keywords: Chanson; Musique

Père Émile Legault: homme de foi et de parole - Jasmin-Bélisle, Hélène (Célébrités / Collection biographique, 2000)
Keywords: Action catholique; Communautés religieuses; Congrégation de Sainte-Croix; Legault, Émile; Théâtre

Gérard Barbeau, ''La voix d'or du Québec'' - Hachey, Jean-Marie (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2004)
Keywords: Chanson; Cinéma; Musique

Léandre Brault, fondateur des Petits chanteurs du Mont-Royal - Dupuis, Carl-O (Fides, 2000)
Keywords: Chanson; Congrégation de Sainte-Croix; Oratoire Saint-Joseph

El teatro Playback: talleres de improvisación teatral para la integración de los inmigrantes latinoamericanos en Montreal - Barreto, Gaby (Université de Montréal, 2008)
Keywords: Latino-Américains; Théâtre

L'École littéraire de Montréal et la vie musicale - Lefebvre, Marie-Thérèse (La Vie culturelle à Montréal vers 1900, 2005)
Keywords: Musique; École littéraire de Montréal

Chant et mission en Nouvelle-France, espace et rencontre des cultures - Dubois, Paul-André (Université Laval, 2004)
Keywords: Autochtones; Chanson; Missions; Musique

Les Soirées-Mathieu (1930-1935) - Lefebvre, Marie-Thérèse (Les Cahiers des dix, 2003)
Keywords: Laurendeau, André; Musicien; Musique

Toot Sweet: When Jazz Ruled Montreal - Reynolds, Mark (The Beaver, 2001)
Keywords: Musique; Noirs

Les Noirs et le jazz au Québec - Lelièvre, Denys (Cap-aux-Diamants, 2004)
Keywords: Musique; Noirs

Crisis? What Crisis?: Anglophone Musicmaking in Montreal - Stahl, Geoff (Université McGill, 2003)
Keywords: Anglophones; Musique

Le Black Theatre Workshop de Montréal: un nouveau bilan - Bayne, Clarence (L'annuaire théâtral, 2001)
Keywords: Noirs; Théâtre

Femmes de soir (théâtre); suivi de Contours: réflexion à partir du théâtre africain-américain - Amoni, Emmanuelle (Université du Québec à Montréal, 2000)
Keywords: Africains; Noirs; Théâtre

De l'intime au public: les étudiants et l'activité musicale à Montréal - Barrière, Mireille (La Vie culturelle à Montréal vers 1900, 2005)
Keywords: Cercle Ville-Marie; Musique; Étudiants

Influence de la culture hip-hop québécoise sur les adolescents montréalais d'origine haïtienne - Tessier, Karine (Université du Québec à Montréal, 2008)
Keywords: Danse; Haïtiens; Musique

A Gift for Their Mother: The Saidye Bronfman Centre Theatre. A History - Gold, Muriel (Productions Miri, 2007)
Keywords: Juifs; Théâtre

DE SÈVE, ALFRED - Houle, Jacques-André (Dictionnaire biographique du Canada, 2005)

LASSALLE, EUGÈNE - Barrière, Mireille (Dictionnaire biographique du Canada, 2005)

PELLETIER, ROMAIN-OCTAVE - Vachon, Pierre (Dictionnaire biographique du Canada, 2005)

Le théâtre francophone à Montréal de 1855 à 1880: les causes d'un développement tardif - Laflamme, Jean (Maxime, 2005)
Keywords: Francophones; Théâtre

Le théâtre francophone à Montréal de 1855 à 1880: une institution qui tarde - Laflamme, Jean (Université de Montréal, 2000)
Keywords: Francophones; Théâtre

SAINT-JEAN, IDOLA - Lavigne, Marie; Stanton-Jean, Michèle (Dictionnaire biographique du Canada, 2003)

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens